POLA STRATEGI NAFKAH RUMAHTANGGA PETANI BERBASIS SUMBERDAYA LOKAL DI DESA MANTANGAI HILIR KECAMATAN MANTANGAI - Yuni Erlina (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
The objectives of this research are: (1) To examine the pattern of utilization of agricultural resources based on local resources by households as the source of household income. (2) To examine the pattern of livelihood strategy that is determined as the rationality of the decision of the household household in Mantangai Hilir village. The basic method of research using survey method. The determination of research location was determined purposively in Mantangai Hilir Village, Mantangai District. The aims of the first and second research are analyzed by qualitative approach and described descriptively. The results showed that the pattern of utilization of agricultural resources based on local resources by the households of the farmers are sourced from rubber plantations, wetlands/fiels, yard/other garden, forest land, and swamp and river. The pattern of livelihood strategies in the utilization of local natural resources indirectly implements the cost efficiency principle whereby the livelihood strategy pattern is based on the consideration of the rationality of the household decision of the farmer.